Epidemiological profile of cases of oral and maxillofacial trauma in patients assisted in a hospital in the north of Piauí: a 5-year retrospective study - Antonia Camila Farias; Camila Bruna Coelho de Brito; Almiro Mendes da Costa Neto; Evaldo Sales Leal; Luis Paulo da Silva Dias; Rogério Meneses Ibiapina Coelho (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT Objective: This study aimed to outline the socio-epidemiological profile of patients with facial fractures treated at a state hospital in a medium-sized city in northeastern Brazil. Methods: The medical records of patients who suffered facial trauma treated at the hospital in question in the las five years (2018-2022) were evaluated. Results: In 2021, the highest number of cases were recorded. There was a male predominance (81.00%), the average age was 35.13. The maxillary zygomatic orbit complex was the most affected bone, which represented 28.00%, with motorcycle accidents as the main etiology, osteosynthesis of the maxillary zygomatic orbit complex the most used means of treatment, and Parnaíba the city with the most patients. Conclusion: It is noticed that young adults were more affected, with motorcycle accidents as the main etiology. In this way, oral and maxillofacial trauma could be avoided with the increase of more educational measures in traffic and greater punishment for reckless drivers.